INCLUSIVE STAKEHOLDERS APPROACH: BASIS FOR ACCEPTABLE AND SUSTAINABLE INDUSTRIAL RELATIONS ENVIRONMENT IN NIGERIA - Ogundele, O.J.K.; Olajide, O.T. (European Scientific Journal, ESJ, 2012)
The paper highlights some of the several reforms put in place by the present Civilian administration. It tagged the administration, reforms regime. It contends that several of reforms have far reaching implications for the practice of industrial relations in Nigeria. It observes that the authors of the reforms assume away the impacts of these reforms on the various stakeholders in industrial relations in Nigeria. It highlights the dangers that are already rearing their ugly head as far as industrial relations practice is concerned. It proposes an inclusive stakeholders approach as way of promoting an acceptable and sustainable industrial relations environment in the reform regime. It contends that with this approach organizations or business firms have to be fair, accountable, responsible and transparent towards all stakeholders of the organizations or firms. It notes that the institutional landscapes from which the reforms were adopted for implementation in Nigeria differ considerably and this calls for some inbuilt strategy for sustainability of acceptable industrial relations practice.